Factor structure of post-operative quality of recovery questionnaire (QoR-15): An Italian adaptation and validation - Rosato, Rosalba; Palazzo, Valentina; Borghi, Felice; Camanni, Marco; Puppo, Andrea; Delpiano, Elena Maria; Pellegrino, Luca; Piovano, Elisa; Rizzo, Alessio; Rolfo, Monica; Morino, Mario; Allaix, Marco Ettore; et al. (Frontiers in Psychology, 2023)
Background: The Quality of recovery questionnaire (QoR-15) is an English instrument for measuring quality of recovery in surgical patients, not yet translated and validated in Italian when the Enhanced Recovery After Surgery (ERAS) Piemonte studies were planned. Objective: To produce the Italian version of the QoR-15 questionnaire, to evaluate its factorial structure and to assess the invariance between two types of surgery. Methods: The Italian version (QoR-15I) was obtained translating and adapting the original version to the Italian context. The validation was performed suppling the QoR-15I to 3784 patients enrolled in two parallel stepped wedge cluster randomised trials (ERAS Colon-rectum Piemonte; ERAS Gyneco Piemonte). The factor structure and its invariance between types of surgery was tested using confirmatory bifactor model and multi-group analysis. Comparative fit index (CFI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR) fit indices and their changes between nested models were used to assess the factor structure and the invariance. Results: The bifactor model showed good fit (RMSEA=.049, CFI =.957, SRMR=.036) and provided a general recovery factor and two specific factors for physical and mental recovery. 84% of the common variance is attributable to the general factor, and thus the QoR-15I is sufficiently 'one-dimensional' with an adequate reliability (Omega_h=0.70). The Omega_s values for the physical and mental recovery factors were 0.01 and 0.13, respectively. Multigroup analysis supported configural (RMSEA=.053, CFI=.950, SRMR=.035) and metric invariance (ΔRMSEA=-.004; ΔCFI=-.002; ΔSRMR=.014), whereas the intercept constraint was removed from item 15 to obtain acceptable partial scalar invariance (ΔRMSEA=.002; ΔCFI=.007; ΔSRMR=.004). Construct validity was supported by a negative association of QoR-15I scores with all variables related to worse patient condition and more complex surgery. Conclusion: Our results support the use of the QoR-15I as a valid, reliable, and clinically feasible tool for measuring the quality of recovery after surgery. The results of the confirmatory factor analyses suggest that a unique recovery score can be calculated and support measurement invariance of the QOR-15I across the two type of surgery, suggesting that the questionnaire has the same meaning and the same measurement parameters in colorectal and gynaecologic patients.